Reactive Granulomatous Dermatitis in a Child with Acute Lymphoblastic Leukemia - Hannah C. Tolson; Mariana McCune; Miranda Yousif; David DiCaudo; Elizabeth Dupuy (Hindawi Limited, 2023)
Reactive granulomatous dermatitis (RGD) is an umbrella term to describe a reaction pattern characterized by skin-colored to erythematous papules, plaques, and nodules although other morphologies have been described. RGD has rarely been reported in children, and in this report, we present the case of a 3-year-old girl with acute lymphoblastic leukemia (ALL) who presented with firm, tender nodules, and ulcerated plaques on her extremities. Histopathologic examination showed foci of dense granulomatous inflammatory infiltrates composed of histiocytes, neutrophils, and multinucleate giant cells. The constellation of clinical symptoms, negative infectious workup, and histopathology support the diagnosis of RGD.